INCIDENCE OF HEPATITIS C VIRUS INFECTION IN A SEMI-URBAN COMMUNITY OF SOUTHWESTERN NIGERIA (2014)
Hepatitis C Virus (HCV) infection is an important cause of chronic hepatitis, cirrhosis and hepatocellular carcinoma. Its epidemiology has been well described in developed countries. In Nigeria, previous studies on the virus were hospital-based or point prevalence from which the burden of HCV cannot be accurately determined. A population-based prospective study was therefore designed to assess the burden of HCV infection in a semi-urban community in southwestern Nigeria. A cohort of 490 purposively recruited consenting participants in Saki, a border town in Nigeria were enrolled and followed up for nine years (2003-2012). Blood samples were collected and tested for the presence of HCV antibodies using the ELISA technique from each participant at baseline, one year, 2 years and 9th year. The participants included 299 male and 191 female members of two occupational groups, auto-mechanics (n=236) and fashion designers (n=254) with age range of 15 to 65 years (median age=26years). A structured questionnaire was administered to capture information on awareness of HCV infection as well as predisposing factors including sharing of sharp objects, transfusion of blood and blood product, polygamy and multiple sexual partnership. The cohort was continuously provided education on prevention of sexually transmitted diseases and blood borne pathogens during the follow-up period. Data were analysed using descriptive statistics and ANOVA at p=0.05. Incidence of infection was reported as number of HCV cases/1000 person years. The rate of HCV infection at baseline was 8.4%. A total of 27 new cases of infection were identified in the cohort giving an overall incidence of 27.8 per 1000 person years. Incidence of HCV increased from first to the second (9.0 Vs 24.7 per 1000 person years) year but declined thereafter (11.3 per 1000 person years). Incidence of the infection increased with age and peaked among persons 45-54 years (34.5 and 38.5 per 1000 person years). The incidence was higher among male than female (21.2 Vs 14.5 per 1000 person years). Incidence in both male and female groups increased from first to second point but declined sharply thereafter. Incidence of HCV infection was higher among auto-mechanics (31.4 per 1000 person years), a male occupational group than fashion designers (23.9 per 1000 person years), a female dominated occupational group. Similarly, HCV incidence was higher in male (49.9 per 1000 person years) than female (14.6 per 1000 person years) members of the fashion designer group (Risk Ratio = 2.7, CI=1.32-5.87). The only significant risk factor identified was sharing of sharp objects (RR=2.4, CI=1.0-5.56, χ20.05:1=4.329, p=0.04). There was a substantial burden of HCV infection in the studied community. Sharing of sharp objects is a significant predisposing factor for HCV infection among the study populations. The high burden of the infection indicates the need for urgent implementation of measures to control HCV infection in Nigeria.